2005
DOI: 10.1103/physrevb.72.245420
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of macroscopic carbon nanotube structures by polymer intercalation: The role of polymer molecular weight and chain conformation

Abstract: Novel polymer nanotube composites were fabricated by intercalating poly͑vinylpyrrolidone͒ into Buckypaper from solution. This was carried out for both low ͑10k g/mol͒ and very high ͑1.3M g/mol͒ molecular weight polymers. Measurements of the polymer mass uptake as a function of time allowed the calculation of diffusion coefficients as 1.66ϫ 10 −9 cm 2 / s and 3.08ϫ 10 −12 cm 2 / s for the low and high molecular weight strands, respectively. Taking into account the molecular weights, comparison of these coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 22 publications
3
79
0
Order By: Relevance
“…For example, buckypapers obtained from dispersions containing SWNTs and surfactants exhibited Young's moduli that fall between 0.5 and 2.3 GPa, tensile strengths within the range 4.7-33 MPa, and ductility ranging from 1-2.5%. 8,[25][26][27] The similarity between the mechanical properties of the buckypapers examined here may be due to the similar size of the dispersants present in the membrane. Consistent with this hypothesis are the results of a recent study that showed that the tensile strength of buckypapers made from SWNTs was significantly improved only when high molecular mass dispersants, such as proteins or polysaccharides, were incorporated into the membranes.…”
Section: Physical Propertiesmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, buckypapers obtained from dispersions containing SWNTs and surfactants exhibited Young's moduli that fall between 0.5 and 2.3 GPa, tensile strengths within the range 4.7-33 MPa, and ductility ranging from 1-2.5%. 8,[25][26][27] The similarity between the mechanical properties of the buckypapers examined here may be due to the similar size of the dispersants present in the membrane. Consistent with this hypothesis are the results of a recent study that showed that the tensile strength of buckypapers made from SWNTs was significantly improved only when high molecular mass dispersants, such as proteins or polysaccharides, were incorporated into the membranes.…”
Section: Physical Propertiesmentioning
confidence: 77%
“…7 An alternative method for preparing CNT membranes is by filtration of dispersions obtained by applying ultrasonic energy to samples containing CNTs and a suitable dispersant. 8 While the resulting buckypapers have a broader distribution of larger pores than those in aligned membranes, this approach offers several advantages. These include greater ease of preparation and avoiding harsh chemicals required to remove the supporting substrates that are generally used to grow aligned membranes on.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many researchers have employed singlewalled and multi-walled carbon nanotubes to enhance the mechanical performance of polymer composite films (Ajayan et al, 2000;Cadek et al, 2004;Frizzell et al, 2005;Wei, 2006). While this study focuses on the piezoresistive characteristics of SWNT-PSS/PVA thin films, mechanical strength strongly influences thin film durability for long-term strain sensing.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…2, NT based films tend to be quite porous. 20 We have calculated the porosity of the films P from the density of films film and the density of CNT NT using 20 P =1− film / NT . The porosity of the SWNT films varied greatly from 42% ͑South Western Nanotechnologies Inc. SWNT in NMP͒ to 76% ͑Nanocyl SWNT in NMP͒.…”
Section: A Film Characterizationmentioning
confidence: 99%